Acute Kidney Injury Masked by Malnutrition: A Case Report and the Problem of Protein. (26th December 2018) - Schwartz, Emily; Hillyer, Robert; Foley, Jessica; Willcutts, Kate; Ziegler, Jane
Abstract: Acute kidney injury (AKI) is common among critically ill patients. There are a number of nutrition considerations in the management of AKI, including fluid balance, electrolyte and acid‐base disturbances, protein provision, and management of comorbid conditions. The optimal amount of protein provision for patients with AKI who are not on renal replacement therapy (RRT) has been a topic of debate for years. Excessive protein provision may contribute to azotemia in these patients, but inadequate protein intake may harm nutrition status and result in poorer clinical outcomes. This review discusses a patient case of AKI masked by malnutrition and muscle loss and reviews the current literature on optimal protein intake in AKI (not on RRT). Based on a structured search strategy, 4 articles were reviewed. We conclude that the available evidence suggests that significant restrictions in protein intake are not necessary for those critically ill patients with AKI. However, the studies reviewed here showed significant heterogeneity in protein dose and delivery, estimation of protein needs, patient population, and definition of AKI, and thus further research is needed to systematically determine the optimal dose of protein for critically ill adults with AKI.